A Study on Marketing Strategies of Catering Enterprises from a Customer centric Perspective– Taking Ningbo Wurong Famous Kitchen Catering Co., Ltd. as an Example - Sun, Hezhen (International Journal of Global Economics and Management, 2024)
With the increasingly fierce market competition and the diversification of consumer demand, enterprises no longer only focus on the product itself, but also need to put customer needs and satisfaction at the core position, and build a customer-oriented marketing strategy. This article explores the problems in the customer-oriented marketing strategy of Ningbo Wurong Famous Kitchen and Catering Co., Ltd., and proposes targeted measures to optimize marketing strategies, providing reference and inspiration for other catering industries, promoting the entire industry to move towards a customer-oriented marketing concept, improving consumer satisfaction, and promoting sustainable development of the enterprise.